2006
DOI: 10.1093/schbul/sbl038
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation in Skin Flush Response to Niacin Patch Among Schizophrenic Patients and Their Nonpsychotic Relatives

Abstract: Though a reduced flush response to niacin has been found in schizophrenic patients, whether it is a vulnerability indicator to schizophrenia remains little known. We aimed to examine the familial aggregation in niacin flush response among schizophrenic patients and their nonpsychotic relatives. In a sample of 153 schizophrenia probands, 217 parents, 70 siblings, and 94 normal subjects, 3 concentrations (0.001 M, 0.01 M, and 0.1 M) of niacin were applied to the forearm skin and the flush response was rated at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 30 publications
1
39
0
2
Order By: Relevance
“…Lin et al demonstrated impaired flush response to niacin in patients' relatives (31). These investigators further found more impairment in families with more than one sibling with schizophrenia (multiplex families) compared to those families with one 6…”
Section: Discussionmentioning
confidence: 96%
“…Lin et al demonstrated impaired flush response to niacin in patients' relatives (31). These investigators further found more impairment in families with more than one sibling with schizophrenia (multiplex families) compared to those families with one 6…”
Section: Discussionmentioning
confidence: 96%
“…If such drugs do tend to normalize niacin sensitivity, then the potential bias in patient sample would be to underestimate the prevalence or magnitude of the niacin response abnormality in SZ. Taken together, comparing the niacin-induced flushing between medicated and unmedicated SZ patients, or unmedicated, non-psychotic relatives, suggests that the niacin response abnormality in SZ is not an artifact of antipsychotic medications (Chang et al, 2009;Lin et al, 2007;Maclean et al, 2003;Shah et al, 2000).…”
Section: The Niacin Response Abnormality Is Not An Artifact Of Medicamentioning
confidence: 99%
“…2 Depending on the criteria to define nonresponse, the prevalence estimates of impaired flush response to the niacin skin patch in schizophrenia patients ranged from 49% to 90%, whereas those in healthy controls ranged from 8% to 64%. [8][9][10] The impaired niacin flush response was specific to schizophrenia and not observed in depression, 11 bipolar disorder, [12][13][14] or autism. 15 One study in healthy subjects showed that age and gender might be associated with the niacin flush response.…”
Section: Introductionmentioning
confidence: 94%
“…16 The impaired niacin flush response in schizophrenia patients was not influenced by medication status, 17,18 antipsychotic drug doses, 14,19 or substance use such as tobacco smoking, 13,14,17 coffee drinking, 14 or alcohol consumption. 14,17 Attenuated niacin flush response has also been demonstrated in nonpsychotic first-degree relatives of patients with schizophrenia, 9,17,20 with a heritability of 47% to 54%. 9 Greater familial loading for schizophrenia was associated with more impairment in flush response to niacin.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation